Effect of a Psychological Empowerment Program for Nursing Managers on the Management Skills of Nursing Students - Hormat Sadat Emamzadeh Ghasemi; Fatemeh Hajibabaee; Abolfazl Sobati; Zahra Najm Zadeh; Hasan Khosravi (نشریه پرستاری ایران, 2023)
Background & Aims Special attention should be paid to empowering healthcare providers, including nurses. Empowerment as the clinical skill is an important goal of nursing education. The present study aims to determine the effect of a nursing manager psychological empowerment program on the management skills of nursing students. Materials & Methods This interventional study was conducted in Imam Khomeini Hospital in Tehran, Iran. Participants were 84 students in nursing management internship from Tehran University of Medical Sciences and 19 nursing managers. The nursing students were divided into two control (n=42) and intervention (n=42) groups. The intervention was a psychological empowerment program for nursing managers. After intervention, the management skills of students was assessed using a checklist completed by observation and interviewing ward supervisors. Data were analyzed in SPSS software, version 16. Results The management skills of students in the intervention group significantly increased after receiving the empowerment program by 0.274 units. Conclusion Psychological empowerment of nursing managers can improve the management skills of nursing students. The results of this study can be used to persuade nursing managers to receive psychological empowerment training, which can lead to psychological improvement of the work environment, nurses and nursing students.